An Analysis of The Extent of Strategic Entrepreneurships’ Dimensions which applied by the leaders of The National Security Advisory - Abdulhussein Kzar *, Alaa; Jassim Mohammed , Alyaa (Journal of Economics and Administrative Sciences, 2024)
Strategic entrepreneurship is one of the contemporary administrative trends that elevate the status of organizations by enhancing their level of performance, and its importance is particularly clear for security organizations. The current research aims to diagnose the level of practice of strategic Entrepreneurship in the National Security Advisory in Iraq. The research community was represented by the administrative leaders of the National Security Advisory, and the research included a sample of (133) of the leaders of the surveyed Advisory, and the questionnaire was the main tool for collecting data and information related to the research. The current research adopted the descriptive analytical approach, being the most appropriate for the research as it is embodied in follow-up, investigation, and codification in a qualitative way to know the phenomenon in terms of subject and content, and to reach results and generalizations that help in understanding reality, and a number of statistical methods were used, including the mean, standard deviation, coefficient of variation, and percentages, Correlation coefficient and regression coefficient, through the statistical program (SPSS). The research reached a set of conclusions, the most prominent of which was the interest of the National Security Adviser in entrepreneurial culture, which raises the level of strategic Entrepreneurship, resulting from strengthening its position through the ability to make decisions and follow up on its implementation carefully, in addition to having a clear philosophy through which it attracts promising ideas in a high way.